The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.jpra.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma arising in a skin graft donor site following melanoma extirpation at a distant site: A case report and review of the literature

Abstract: s u m m a r yThe development of both squamous cell carcinoma (SCC) and keratoacanthoma (KA) in donor sites following split thickness skin graft harvest are rare complications reported in the literature. Management of such cases requires a precise distinction between keratoacanthoma and SCC and knowledge of the degree of differentiation. We describe the case of a 48-year-old male who developed a squamous cell carcinoma with features of KA within a donor site on his right thigh. This developed six weeks followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…In our review of the literature, we found a total of 16 documented cases. [5][6][7][8][9][10] Our case report represents a de novo occurrence of a well differentiated SCC at a skin graft donor site for reconstruction of chronically infected bilateral hip wounds. It can be inferred that our patient's chronic wounds were a factor for the development of SCC at the donor site.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In our review of the literature, we found a total of 16 documented cases. [5][6][7][8][9][10] Our case report represents a de novo occurrence of a well differentiated SCC at a skin graft donor site for reconstruction of chronically infected bilateral hip wounds. It can be inferred that our patient's chronic wounds were a factor for the development of SCC at the donor site.…”
Section: Discussionmentioning
confidence: 87%
“…Five of the previous case reports found SCC in skin graft donor sites in patients who were undergoing reconstruction with skin grafting for resected skin cancers, which indicates a potential relationship between the original cancer and the SCC arising at the donor site. [5][6][7][8][9] One case report demonstrated the implantation of SCC after using the same hollow bore needle for injection in both the area around the skin cancer and the donor site, indicating the cancer may have seeded into the donor site. 6 Other case reports describe patients who developed SCC at the skin graft donor sites who had undergone reconstruction after burns.…”
Section: Discussionmentioning
confidence: 99%
“…La tasa estimada de recidiva local en los injertos de piel en el sitio de melanoma primario es del 1 al 8%, 10 por lo que se han considerado distintas maniobras preventivas para el desarrollo de melanoma en el sitio donante, variando desde exámenes dermatoscópicos rigurosos del área donante, detección de tirosina hidroxilasa (mRNA) mediante RT-PCR, biopsia linfática, inmunohistoquímica para antígeno S100, HMB-45 y p53. 11 Tenemos la teoría de que se crea una obstrucción de la función inmunológica en referencia a los inmunomarcadores, los que al encontrarse con una obstrucción, que en este caso específico podrían ser las secuelas cicatrízales de maduración, podrían obstruir o ralentizar el proceso en el que se detecta y ataca las células tumorales. También se han registrado casos en los que no sólo el sitio receptor es el afectado, también el sitio donante; en dichos casos se hace referencia al mecanismo de diseminación hematógena y de contaminación y esto se refuerza con la presencia de antecedentes de uso de agentes biológicos para el manejo de cáncer; dicho uso activa los oncogenes BRAF V600E y C-KIT, los cuales son bien conocidos como precursores importantes para el desarrollo de melanoma cutáneo.…”
Section: Discussionunclassified
“…También se han registrado casos en los que no sólo el sitio receptor es el afectado, también el sitio donante; en dichos casos se hace referencia al mecanismo de diseminación hematógena y de contaminación y esto se refuerza con la presencia de antecedentes de uso de agentes biológicos para el manejo de cáncer; dicho uso activa los oncogenes BRAF V600E y C-KIT, los cuales son bien conocidos como precursores importantes para el desarrollo de melanoma cutáneo. [9][10][11]…”
Section: Discussionunclassified
“…ESCC have been reported to arise at the sites of skin surgery, including the area affected by the primary tumor and split thickness skin graft (STSG) donor and recipient sites [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The best therapeutic option for ESCC after surgery in our opinion is still a challenge.…”
Section: Introductionmentioning
confidence: 99%